2018
DOI: 10.1186/s12967-018-1427-5
|View full text |Cite
|
Sign up to set email alerts
|

Low dose Naltrexone for induction of remission in inflammatory bowel disease patients

Abstract: BackgroundAround 30% of patients with inflammatory bowel disease (IBD) are refractory to current IBD drugs or relapse over time. Novel treatments are called for, and low dose Naltrexone (LDN) may provide a safe, easily accessible alternative treatment option for these patients. We investigated the potential of LDN to induce clinical response in therapy refractory IBD patients, and investigated its direct effects on epithelial barrier function.MethodsPatients not in remission and not responding to conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 40 publications
(45 reference statements)
0
49
0
5
Order By: Relevance
“… 101 103 One of these studies showed that naltrexone alleviated endoplasmic reticulum stress in organoids of patients with IBD after treatment with inflammatory stimuli. 104 Interleukin-22 has shown promise as a promising target for ulcerative colitis therapy due to its role in epithelial homeostasis and repair, which lead Patnaude and colleagues 105 107 to trial treatment of inflammation-stimulated organoids with IL-22 that showed improved epithelial regeneration and production of membrane mucus. Han and colleagues 108 took this idea a step further and microinjected patient-derived fecal supernatants with the probiotic Lactobacillus rhamnosus .…”
Section: Methodsmentioning
confidence: 99%
“… 101 103 One of these studies showed that naltrexone alleviated endoplasmic reticulum stress in organoids of patients with IBD after treatment with inflammatory stimuli. 104 Interleukin-22 has shown promise as a promising target for ulcerative colitis therapy due to its role in epithelial homeostasis and repair, which lead Patnaude and colleagues 105 107 to trial treatment of inflammation-stimulated organoids with IL-22 that showed improved epithelial regeneration and production of membrane mucus. Han and colleagues 108 took this idea a step further and microinjected patient-derived fecal supernatants with the probiotic Lactobacillus rhamnosus .…”
Section: Methodsmentioning
confidence: 99%
“…Clinical evidence covers a broad range of sources, from initial case reports [38,39,40] to more recent randomized controlled trials [41,42]. Low-dose naltrexone could be useful for states involving chronic inflammation or immune dysregulation [43], such as Crohn’s disease [44] and fibromyalgia [41].…”
Section: Low-dose Naltrexone In Clinical Medicinementioning
confidence: 99%
“…U niektórych pacjentów cierpiących na stwardnienie rozsiane i poddanych terapii LDN zaobserwowano pierwotną małopłytkowość immunologiczną (dawniej nazywaną samoistną plamicą małopłytkową (ang. idiopathic thrombocytopenic purpura, ITP), która mogła być wynikiem idiosynkrazji będącej stanem zwiększonej odczynowości organizmu na określony lek, związanej z osobniczą wrażliwością [7,39].…”
Section: Bezpieczeństwo Stosowaniaunclassified